Fault diagnosis of PID in crystalline silicon photovoltaic modules through I-V curve. (November 2021) - Ma, Mingyao; Wang, Haisong; Xiang, Nianwen; Yun, Ping; Wang, Hanyu
Abstract: Potentially induced degradation (PID) faults in crystalline silicon photovoltaic modules are a well-known problem. Traditional detection methods are time-consuming and expensive. In order to quickly detect the PID PV modules online, we investigate and collect the PID PV modules in several large PV power plants. The I-V characteristics of the PID modules are tested. The test results show that the open circuit voltage of PID modules has a significantly decline than that of the normal modules. In addition, the open circuit voltage has a large difference under high and low irradiance, and the reason of this feature is analyzed. A method for online diagnosis of PV module PID faults through I-V curve is proposed, and it has been verified that the method is effective for PID faults. Highlights: PID fault is one of the most common faults of PV modules and it is difficult to be detected. The EL image of the PID modules is different from that of the degraded modules. The fill factor (FF) of PID modules is lower than normal modules. The open circuit voltage of PID modules is lower than normal modules. The open circuit voltage of PID module under low irradiance is lower than that under high irradiance.